2011
DOI: 10.1057/jit.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

IT Alignment and the Boundaries of the IT Function

Abstract: This study applies the concept of organizational boundary to examine how outsourcing and the management of external and internal boundaries of the information technology (IT) function impact IT alignment. The article argues that by decreasing the governance costs for the less strategic IT transactions, IT outsourcing enables the IT function, and IT management particularly, to focus more on aligning the IT activities and plans with business strategies and priorities, and thereby improve IT alignment. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…After two reminders, we received 149 completed questionnaires, of which 132 data sets remained for analysis after 17 were removed because of missing values 3 (indicating a response rate of 10.9%). Since collecting data from top managers is challenging, the sample size is reasonable and comparable to other surveys in the alignment literature (e.g., Kearns and Lederer, 2003;Bergeron et al, 2004;Valorinta, 2011).…”
Section: Methodsmentioning
confidence: 88%
“…After two reminders, we received 149 completed questionnaires, of which 132 data sets remained for analysis after 17 were removed because of missing values 3 (indicating a response rate of 10.9%). Since collecting data from top managers is challenging, the sample size is reasonable and comparable to other surveys in the alignment literature (e.g., Kearns and Lederer, 2003;Bergeron et al, 2004;Valorinta, 2011).…”
Section: Methodsmentioning
confidence: 88%
“…IS research found a large array of artefacts that function as BOs, including business process diagrams [11], requirement specifications [5,22], enterprise architecture designs and models [12], information systems [11,13], and prototypes [2]. These artefacts can have different meanings within the work communities, while they are expected to provide a representational structure that is common to all these groups "so that they are recognizable to them and can serve as a means of translation" [23].…”
Section: Boundary Objectsmentioning
confidence: 99%
“…Moreover, the knowledge pools constitute the boundaries between the CoPs that need to be bridged in order to develop shared understanding about the contradictions and how the IS may resolve them (i.e., how to implement IS effectively) [9]. For this purpose, usually multiple instruments and projectrelated artefacts such as requirement elicitation methods, business process models and enterprise architecture designs are employed [5,11,12,22]. From an AT perspective, particular candidates for BOs are those project-related artefacts and concepts that are utilized in the business and IS implementation activity and thus link both activity systems to a greater or lesser extent.…”
Section: An Activity Theoretical View On Bosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they add that if alignment is so easy and trivial, it is strange that it has been CIO's top concern for such a long time and that it still attracts considerable attention from researchers. One reason for why alignment have been and still is in focus is presented by Valorinta (2011), who claims that alignment is an on-going organizational process that requires a lot from the ones involved, especially if the alignment should be successful. With this statement, Valorinta more or less adds to the understanding that alignment enhances good business performance.…”
Section: A Literature Review On Alignmentmentioning
confidence: 99%